Test timed up and go and its correlation with age and functional exercise capacity in asymptomatic women - Wesley de Oliveira Vieira; Thatiane Lopes Valentim di Paschoale Ostolin; Mateus Ferreira; Evandro Fornias Sperandio; Victor Zuniga Dourado
Abstract Introduction: The Timed Up and Go test (TUG) is widely used and valid in chronic patients, but rarely addressed in asymptomatic individuals. Objective: To assess the reliability, the age-related changes and the correlation between TUG and the Functional Exercise Capacity (FEC) adjusted for non-institutionalized middle-aged and elderly women. Methods: Ninety-eight women (57 ± 10 years) were selected and stratified into age groups. We have performed the tests TUG, Berg Balance Scale (BBS) and evaluation of usual gait speed (UGS). Fifty-eight participants (57 ± 10 years) also performed incremental shuttle walk test (ISWT). Results: Worse performance in TUG (p < 0,05) for participants aged ≥ 70 years for age groups 40-49 and 50-59 years. The reliability of TUG was excellent between the first and second TUG (intraclass correlation coefficient, 0.933; confidence interval of 95%, from 0.901 to 0.955) and between the second and third TUG (0.958, 0.938 to 0.972). The group of 58 participants who underwent further the ISWT, TUG correlated significantly (p <0.05) with ISWT (r = -0.72), VUM (r = -0.54) and BBS (r= 0.58). A multiple linear regression analysis selected TUG (R2 = 0.517) and VUM (R2 = 0.083) as determinants of FEC. Conclusion: TUG adapted for asymptomatic women is reliable and able to assess the decline of physical mobility with advancing age and it also crucial to the FEC.